Poor, unemployed, and politically inactive? - Martin Kroh; Christian Könnecke (DIW Economic Bulletin, 2014)
People with low incomes and job seekers are less interested and active in politics than people above the at-risk-of-poverty threshold and the working population. Compared to other European democracies, Germany has slightly above-average levels of inequality of political participation. Data from the Socio-Economic Panel Study (SOEP) suggest that this inequality has followed an upward trend over the last three decades. The data also indicate, however, that the unemployed do not reduce their political participation only as a result of losing their job, nor do those affected by poverty do so due to loss of income. Rather, the lower levels of political participation existed prior to these events and can be attributed to the social backgrounds of those affected.
Keywords: D72; I32; J64; 330; political participation; inequality; poverty; unemployment; SOEP